DOES TAX EVASION EQUAL ZERO IN THE PRESENCE OF TECHNOLOGICAL ADVANCEMENTS? EVIDENCE FROM PALESTINE. THEORETICAL INVESTIGATION - Shadi Emad Areef Alhaleh, Puji Handayati, Hua Wang (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study aims to investigate whether technological advancements can achieve substantial progress in tax. Practically, the study provides new criteria, procedures, and guidelines that could strengthen and enhance better understandings of, and new insights into the technology field which lead to attaining substantial progress in the Palestinian tax departments. Theoretically, this paper contributes to providing the tax departments with contemporary disclosures and further clarifications on new advanced technologies. The findings of this study can assist decision-makers in the Palestinian tax departments in improving practical plans that may accelerate and expand the adoption of new technologies